Improvement Of Speaking Skills Based on Collaborative Learning Models in Students Class V Elementary School - Sitiyul Setiawati; Ulfah; Sukma; Ida Nur'aeni; Juniati (Universitas Islam Negeri Palopo, 2025)
Problems in the research on Improving Speech Skills Based on Collaborative Learning Model in Grade V Students of Elementary School. This study aims to determine the improvement of speaking ability based on the Collaborative Learning Model in Grade V Students of Elementary School. This type of research is Classroom Action Research (PTK). The subjects in this study are grade V students of Elementary School. This type of research is class action research or PTK using the Kemmis and Mc Taggart research model, namely planning, implementation of actions, observation, and reflection The subject of this research is grade V students of Elementary School. The data collection technique uses the performance test technique. The data analysis technique in this study uses qualitative and quantitative data analysis. The results of this study were obtained in cycle I showing that there was an increase in speaking ability in the aspects of fluency, sentence structure, vocabulary, intonation and pronunciation were very good. This increase was seen in cycle I and cycle II increased from 5% to 81%. Based on the average score obtained by students in cycle I is 75 and in cycle II the average score obtained by students is 80. From these results, it can be concluded that the implementation of the collaborative learning model can improve the speaking ability of grade V students of Elementary School.